In-situ polymerization electrolyte preparation method
Through the in-situ polymerization electrolyte preparation method, the problem of poor contact performance between the solid electrolyte and the electrode interface in lithium metal solid-state batteries is solved, and the battery performance and safety enhancement are improved.
Patent Information
- Application Number
- CN202510101218.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The solid-solid-contact performance of the interface between the inorganic solid electrolyte and the electrode in lithium metal solid-state batteries is poor, resulting in large interface impedance, affecting battery performance and cycling stability.
Using the electrolyte preparation method of in-situ polymerization, an elastomeric polymer monomer is formed by adding a crosslinking agent and a nitrile additive under the protection of argon, then adding lithium salt and a radical polymerization initiator, followed by adding cationic polymerization monomer and a flame retardant initiator, cationic polymerization and heat-induced radical polymerization are performed to obtain a bipolymer electrolyte.
It significantly improves the interface performance, safety performance and electrochemical performance of the electrolyte, improves the rate performance, cycle life and energy density of the battery, and effectively prevents the growth of lithium dendrites, improving the safety and cycle stability of lithium metal batteries.
Smart Images

Figure CN119890432A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solid electrolytes, and in particular to a method for preparing an electrolyte by in-situ polymerization. Background Art
[0002] With the rapid development of science and technology and the urgent market demand for high energy density and high safety performance energy storage devices, traditional lithium-ion batteries have gradually shown their limitations. The liquid electrolyte in lithium-ion batteries is flammable and has the risk of leakage, which not only limits its application in fields with high safety requirements, but also increases safety hazards during use. In addition, the theoretical specific capacity of graphite negative electrodes is limited, which further hinders the improvement of lithium-ion battery energy density.
[0003] In view of this, lithium metal is regarded as an ideal choice for negative electrode materials due to its extremely high theoretical energy density and low reduction potential. In order to improve the safety performance and energy density of lithium-ion batteries at the same time, researchers have proposed using solid electrolytes to replace traditional liquid electrolytes. This strategy is expected to significantly meet the dual needs of high energy density and high safety of future energy storage devices.
[0004] However, lithium metal solid-state batteries still face many challenges in practical applications. Among them, the solid-solid contact problem between the inorganic solid electrolyte and the electrode interface is particularly prominent. The rigidity and brittleness of the inorganic solid electrolyte lead to poor interface contact performance with the electrode and large interface impedance, which in turn affects the performance and cycle stability of the battery. To address this problem, polymer electrolytes have attracted widespread attention due to their good flexibility and interface properties. Among them, the in-situ generated solid electrolyte precursor is liquid, which can fully infiltrate the interface between the electrode and the electrolyte, and then undergoes in-situ polymerization under the action of thermal initiation or ultraviolet light.
[0005] At present, in-situ generated polymer electrolytes are usually prepared by free radical polymerization. Free radical polymerization introduces additional initiators and uses the double bonds in the monomers to open and generate polymer electrolytes during the polymerization process. The elastomeric solid electrolytes prepared by this method have shown certain potential in lithium metal solid-state batteries, especially in solving the problem of volume change during charging and discharging. However, polymer electrolytes prepared by free radical polymerization also face some challenges. For example, the polybutyl acrylate system, which has been studied more, has excellent cycling performance in the assembled lithium metal symmetric battery, but the contact performance with the positive electrode micro-nanoparticles is poor, which makes it difficult to improve its rate performance. In addition, the system still has the problem of flammability, which limits its application in fields with high safety requirements.
[0006] In order to improve the safety performance of polymer electrolytes, researchers have tried to add liquid phosphate monomers to the system. However, although the introduction of liquid electrolytes improves safety performance to a certain extent, it also reduces the mechanical properties of the polymer and weakens the ability to inhibit lithium dendrites, thereby reducing the cycle performance of lithium metal batteries. Summary of the invention
[0007] The embodiments of the present application solve the problems raised in the background art by providing a method for preparing an electrolyte by in-situ polymerization.
[0008] The present application provides an in-situ polymerized electrolyte preparation method, comprising:
[0009] In an argon atmosphere, a cross-linking agent and a nitrile additive are respectively added to the elastomer polymer monomer to completely dissolve the monomers, thereby obtaining a first solution;
[0010] Adding a first lithium salt to the first solution, wherein the first lithium salt is lithium bis(trifluoromethanesulfonyl imide), lithium hexafluorophosphate or lithium perchlorate, stirring evenly, then adding a second lithium salt, wherein the second lithium salt is lithium difluorooxalatoborate, lithium fluoride or lithium nitrate, continuing to stir evenly, then adding a free radical polymerization initiator to obtain an elastomeric polymer electrolyte precursor solution;
[0011] Adding a cationic polymerizable monomer to the elastomeric polymer electrolyte precursor solution and stirring it uniformly, then adding a flame retardant initiator thereto and stirring it uniformly again to obtain a dual polymer electrolyte precursor solution;
[0012] The dual polymer electrolyte precursor solution is added into the battery, and a cationic polymerization reaction is carried out at room temperature. After standing for 10-24 hours, free radical polymerization is initiated by heating to obtain an in-situ polymerized dual polymer electrolyte.
[0013] In a possible implementation, the dual polymer electrolyte precursor solution is added to a battery, further comprising:
[0014] The coating is applied to the positive electrode surface of the battery by dripping, coating or a combination of dripping and coating.
[0015] In a possible implementation, the elastomeric polymer monomer includes at least one of methacrylic acid, ethyl acrylate, ethyl methacrylate, butyl acrylate, and hexyl acrylate.
[0016] In a possible implementation, the cross-linking agent includes a bifunctional monomer.
[0017] In a possible implementation, the bifunctional monomer includes at least one of polyethylene glycol diacrylate and tripropylene glycol diacrylate.
[0018] In a possible implementation, the mass percentage of the bifunctional monomer to the elastomeric polymer monomer is 1%-10%.
[0019] In a possible implementation, the concentration of the first lithium salt is 0.5-3 mol / L; the concentration of the second lithium salt is 0.05-0.3 mol / L; and the mass percentage of the free radical polymerization initiator and the elastomeric polymer monomer ranges from 0.05 wt % to 2 wt %.
[0020] In a possible implementation, the nitrile additive is succinonitrile or glutaronitrile; and the free radical polymerization initiator is azobisisobutyronitrile.
[0021] In a possible implementation, the cationic polymerization monomer is a cyclic monomer, and the cationic polymerization monomer includes at least one of dioxane, trioxane, 1,3-dioxolane, tetrahydrofuran and butoxycyclic ring, and the volume percentage of the cationic polymerization monomer and the elastomeric polymer monomer is 5 vol% to 50 vol%.
[0022] In a possible implementation, the flame retardant initiator includes at least one of tris(pentafluorophenyl)boron or tris(hexafluoroisopropyl)borate; and the mass percentage of the initiator to the cationic polymerization monomer is in a range of 1 wt % to 5 wt %.
[0023] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects:
[0024] The present application embodiment provides an in-situ polymerized electrolyte preparation method. First, since the method does not require the additional introduction of liquid components, the optimization of electrolyte performance is achieved without significantly reducing the mechanical strength of the electrolyte. During the preparation process, a cationic polymerization product is first generated at room temperature, the viscosity of the precursor system increases, and then the elastomeric polymer monomer undergoes thermally initiated free radical polymerization, accompanied by an increase in viscosity, which ensures the uniformity of the free radical polymerization and suppresses volume shrinkage. This characteristic not only maintains the mechanical strength of the electrolyte, but also effectively improves the interface performance between the electrolyte and the positive micro-nano particles. The improvement of the interface performance directly enhances the rate performance of the battery, allowing the battery to maintain higher efficiency and stability during rapid charge and discharge.
[0025] Secondly, by introducing a flame-retardant initiator and introducing the flame-retardant unit into the polymer chain through cationic polymerization, this method significantly improves the safety performance of the electrolyte and avoids the side reactions caused by liquid flame retardants. When the battery encounters abnormal conditions such as short circuit or overheating, the electrolyte exhibits excellent flame retardant properties and is not easy to burn or explode, thereby effectively protecting the safety of the battery and surrounding equipment. This improvement in safety performance is undoubtedly of vital importance for key application areas such as electric vehicles and energy storage systems.
[0026] Finally, this method successfully constructed a stable dual polymer electrolyte network structure by in-situ polymerization. This unique network structure not only improves the ionic conductivity and electrochemical stability of the electrolyte, but also significantly enhances its mechanical strength. At the same time, the interweaving of the dual polymer network further improves the interfacial compatibility between the electrolyte and the electrode, effectively reducing the interfacial impedance. The optimization of these properties works together to reduce the performance degradation of the battery during the charging and discharging process, extend the cycle life of the battery, and increase the energy density of lithium metal batteries. Especially in the field of lithium metal batteries, the in-situ polymerized electrolyte exhibits a significant inhibitory effect, effectively preventing the growth of lithium dendrites. Lithium dendrites are one of the main causes of internal short circuits and capacity loss in lithium metal batteries. The electrolyte prepared by this method can significantly reduce the probability of lithium dendrite formation, thereby improving the safety and cycle stability of lithium metal batteries.
[0027] In summary, the in-situ polymerized electrolyte preparation method provided in the embodiments of the present application significantly improves its interface performance, safety performance and electrochemical performance while maintaining the mechanical strength of the electrolyte. These technical effects work together to improve the rate performance, cycle life and energy density of the battery, injecting new vitality into the development of new energy storage devices such as lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings required for use in the description of the embodiments of the present application. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0029] Figure 1 A flow chart of the in-situ polymerized electrolyte preparation method provided in an embodiment of the present application;
[0030] Figure 2a A schematic diagram of adding the dual polymer electrolyte precursor solution provided in an embodiment of the present application into a battery;
[0031] Figure 2bA schematic diagram of the interior of a battery after a cationic polymerization reaction provided in an embodiment of the present application;
[0032] Figure 2c A schematic diagram of the interior of a dual polymer electrolyte battery provided in an embodiment of the present application;
[0033] Figure 3a and Figure 3b They are flame retardant performance diagrams of Example 1 and Comparative Example 1 provided in the embodiments of the present application, respectively;
[0034] Figure 4 The magnification diagram of Example 1 and Comparative Example 1 provided in the examples of the present application;
[0035] Figure 5 The impedance spectra of Example 1 and Comparative Example 1 provided in the embodiments of the present application.
[0036] Icons: 1-positive electrode current collector; 2-positive electrode active material; 3-conductive additive; 4-dual polymer electrolyte precursor solution; 5-support membrane; 6-lithium metal anode; 7-flame retardant cationic linear polymer; 8-free radical polymerization elastomeric electrolyte precursor; 9-dual polymer electrolyte; 10-positive electrode-dual polymer electrolyte interface. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0038] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship indicated by the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc. is based on the orientation or positional relationship shown in the drawings, and is only for the convenience of describing the embodiments of the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. The terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance. In addition, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0039] The present application provides a method for preparing an electrolyte by in-situ polymerization, such as Figures 1 to 5 The preparation method comprises the following steps S1-S4:
[0040] S1: Under an argon protection atmosphere, a cross-linking agent and a nitrile additive are respectively added to the elastomeric polymer monomer to completely dissolve them, thereby obtaining a first solution.
[0041] It should be noted that under the protection of argon, the crosslinking agent can be more evenly dispersed in the elastomer polymer monomer, which creates favorable conditions for the subsequent crosslinking reaction, making it more sufficient and uniform. At the same time, the addition of nitrile additives is intended to improve the ionic conductivity and voltage range of the polymer electrolyte.
[0042] Argon, as an inert gas, has the characteristic of being able to effectively isolate impurities such as oxygen and moisture in the air, preventing them from having unexpected chemical reactions with elastomer polymer monomers, crosslinking agents and nitrile additives, thereby significantly improving the chemical stability of the final product. Therefore, under the protective atmosphere of argon, the crosslinking agent and nitrile additives are added to the elastomer polymer monomer and completely dissolved. This process can not only improve the stability and crosslinking effect of the material, but also enhance the weather resistance of the material.
[0043] S2: Add a first lithium salt to the first solution, the first lithium salt is lithium bis(trifluoromethanesulfonyl imide), lithium hexafluorophosphate or lithium perchlorate, stir evenly and then add a second lithium salt, the second lithium salt is lithium difluorooxalatoborate, lithium fluoride or lithium nitrate, continue to stir evenly and then add a free radical polymerization initiator to obtain an elastomeric polymer electrolyte precursor solution.
[0044] Specifically, the introduction of high-conductivity lithium salts such as lithium bis(trifluoromethanesulfonyl imide) and lithium hexafluorophosphate is intended to improve the overall conductivity of the electrolyte, which is crucial to ensuring the high efficiency of ion transport within the battery. The addition of modified lithium salts such as lithium difluorooxalatoborate can further enhance the thermal and chemical stability of the electrolyte, thereby improving the safety performance of the battery. After the free radical polymerization initiator is evenly dispersed in the solution, it will effectively trigger the polymerization reaction of the elastomeric polymer monomer in the subsequent polymerization step, thereby constructing an elastomeric polymer electrolyte network with a specific structure.
[0045] S3: adding the cationic polymerization monomer to the elastomeric polymer electrolyte precursor solution and stirring it evenly, then adding a flame retardant initiator thereto and stirring it evenly again to obtain a dual polymer electrolyte precursor solution 4.
[0046] It should be noted that the addition of a flame-retardant initiator can introduce flame-retardant elements during the polymerization process, thereby significantly improving the flame retardant properties of the dual polymer electrolyte 9, which is crucial to improving the safety performance of the battery, especially under extreme conditions such as high temperature or short circuit, and can effectively prevent thermal runaway and fire risks of the battery.
[0047] S4: Add the dual polymer electrolyte precursor solution 4 into the battery and carry out cationic polymerization at room temperature. After standing for 10-24 hours, initiate free radical polymerization by heating to obtain an in-situ polymerized dual polymer electrolyte 9.
[0048] Furthermore, if Figure 2a As shown, a dual polymer electrolyte precursor solution 4 is injected into the battery, and the solution can fully infiltrate the positive electrode active material 2, the conductive additive 3 and the lithium metal negative electrode 6 on the surface of the positive electrode current collector 1. At the same time, the presence of the support film 5 effectively prevents direct contact between the positive electrode active material 2 and the lithium metal negative electrode 6, thereby avoiding the risk of short circuit.
[0049] In the first step, the present application successfully forms a flame retardant cationic linear polymer 7 through a cationic polymerization reaction at room temperature, such as Figure 2b As shown, this polymer not only forms a close contact with the positive electrode active material 2 and constructs a good interface, but also significantly improves the viscosity of the free radical polymerization elastomeric electrolyte precursor 8. This increase in viscosity plays a key role in effectively suppressing the volume changes that may occur during the free radical polymerization process.
[0050] Then, in the second step, a flame-retardant dual polymer electrolyte 9 is produced by thermally initiated free radical polymerization, such as Figure 2c As shown, the dual polymer electrolyte 9 and the positive electrode active material 2 form an excellent interface contact, namely the positive electrode-dual polymer electrolyte interface 10, which provides a solid guarantee for the high rate performance of the battery.
[0051] Specifically, the dual polymer electrolyte precursor solution 4 of the present application combines two polymerization mechanisms: free radical polymerization and cationic polymerization. Since the initiation conditions of these two polymerization mechanisms are different, step-by-step polymerization can be achieved. First, a reactive flame retardant such as tri(pentafluorophenyl)boron is used as an initiator to start the cationic polymerization reaction at room temperature. By precisely controlling the standing time, it is possible to ensure that the polymerization reaction proceeds step by step, so that the first in-situ polymerization generates a long-chain flame-retardant polymer. Subsequently, the temperature is increased to trigger the second step of thermally initiated in-situ polymerization. At this stage, the monomers of the elastomeric polymer undergo thermally initiated free radical polymerization. Since the viscosity of the solution has increased at this time, this helps to ensure the uniformity of the free radical polymerization. Without significantly reducing the mechanical strength, this step-by-step polymerization method can improve the interfacial properties of the elastomeric electrolyte and the positive electrode micro-nanoparticles, and at the same time enhance its safety.
[0052] It should be noted that the present application embodiment provides an in-situ polymerized electrolyte preparation method. First, since the method does not require the additional introduction of liquid components, the optimization of electrolyte performance is achieved without significantly reducing the mechanical strength of the electrolyte. During the preparation process, cationic polymerization products are first generated at room temperature, the viscosity of the precursor system increases, and then the elastomer polymer monomer undergoes thermally initiated free radical polymerization, accompanied by increased viscosity, to ensure the uniformity of free radical polymerization and suppress volume shrinkage. This characteristic not only maintains the mechanical strength of the electrolyte, but also effectively improves the interface performance of the electrolyte and the positive micro-nano particles. The improvement of interface performance directly enhances the rate performance of the battery, allowing the battery to maintain higher efficiency and stability during rapid charge and discharge.
[0053] Secondly, by introducing a flame-retardant initiator, the flame-retardant unit is introduced into the polymer chain through cationic polymerization. This method significantly improves the safety performance of the electrolyte and avoids the side reactions caused by liquid flame retardants. When the battery encounters abnormal conditions such as short circuit or overheating, the electrolyte exhibits excellent flame retardant properties and is not easy to burn or explode, thereby effectively protecting the safety of the battery and surrounding equipment. This improvement in safety performance is undoubtedly of vital importance for key application areas such as electric vehicles and energy storage systems.
[0054] Finally, this method successfully constructed a stable dual polymer electrolyte 9 network structure by in-situ polymerization. This unique network structure not only improves the ionic conductivity and electrochemical stability of the electrolyte, but also significantly enhances its mechanical strength. At the same time, the interweaving of the dual polymer network further improves the interfacial compatibility between the electrolyte and the electrode, effectively reducing the interfacial impedance. The optimization of these properties works together to reduce the performance degradation of the battery during the charging and discharging process, extend the cycle life of the battery, and increase the energy density of lithium metal batteries. Especially in the field of lithium metal batteries, the in-situ polymerized electrolyte exhibits a significant inhibitory effect, effectively preventing the growth of lithium dendrites. Lithium dendrites are one of the main causes of internal short circuits and capacity loss in lithium metal batteries. The electrolyte prepared by this method can significantly reduce the probability of lithium dendrite formation, thereby improving the safety and cycle stability of lithium metal batteries.
[0055] In summary, the in-situ polymerized electrolyte preparation method provided in the embodiments of the present application significantly improves its interface performance, safety performance and electrochemical performance while maintaining the mechanical strength of the electrolyte. These technical effects work together to improve the rate performance, cycle life and energy density of the battery, injecting new vitality into the development of new energy storage devices such as lithium metal batteries.
[0056] In the embodiment of the present application, adding the dual polymer electrolyte precursor solution 4 into the battery also includes: applying it to the positive electrode surface of the battery by dripping, coating, or a combination of dripping and coating.
[0057] It should be noted that, by dripping or coating, the dual polymer electrolyte precursor solution 4 can be evenly covered on the surface and inside of the positive electrode to form a close contact. This close contact helps to reduce the interface resistance and improve the ion conduction efficiency, thereby significantly improving the electrochemical performance of the battery.
[0058] At the same time, the embodiment of the present application first drops the dual polymer electrolyte precursor solution 4 into the interior of the battery to ensure deep infiltration, and then applies a layer of dual polymer electrolyte precursor solution 4 on the surface of the battery, which can ensure that the interior of the battery is fully infiltrated while ensuring the electrolyte content on the surface.
[0059] In the embodiment of the present application, the elastomeric polymer monomer includes at least one of methacrylic acid, ethyl acrylate, ethyl methacrylate, butyl acrylate, and hexyl acrylate.
[0060] It should be noted that by selecting appropriate elastomeric polymer monomers, the microstructure and porosity of the electrolyte can be regulated, thereby optimizing the ion conduction path and efficiency. This helps to improve the ion conduction performance of the battery, reduce internal resistance, and increase the battery's charge and discharge rate and energy density. These elastomeric polymer monomers have good compatibility with the positive electrode material, which helps to stabilize the electrochemical environment inside the battery and extend the battery's cycle life.
[0061] In the embodiment of the present application, the cross-linking agent includes a bifunctional monomer.
[0062] In the embodiment of the present application, the bifunctional monomer includes at least one of polyethylene glycol diacrylate and tripropylene glycol diacrylate.
[0063] It should be noted that the present application uses bifunctional monomers such as polyethylene glycol diacrylate and tripropylene glycol diacrylate as cross-linking agents, which can significantly improve the cross-linking density of the electrolyte, optimize the microstructure, enhance the interface compatibility and adhesion, improve the safety performance, and provide flexible formula design.
[0064] In the embodiment of the present application, the mass percentage of the bifunctional monomer and the elastomeric polymer monomer is 1%-10%.
[0065] When the mass percentage of the bifunctional monomer and the elastomeric polymer monomer falls within the range of 1%-10%, they can jointly construct an electrolyte network structure with a moderate cross-linking density. This carefully designed network structure not only provides the necessary mechanical support for the electrolyte, effectively preventing the electrolyte from rupturing during the battery charge and discharge cycle, but also ensures good ion conductivity, thereby ensuring the efficient and stable operation of the battery.
[0066] Furthermore, the rational control of the addition ratio of the bifunctional monomer to the elastomeric polymer monomer can not only ensure the excellent performance of the electrolyte, but also help reduce the production cost. Specifically, adding too much elastomeric polymer monomer will lead to an unnecessary increase in production costs, while adding too little elastomeric polymer monomer may weaken the overall performance of the electrolyte.
[0067] In the embodiment of the present application, the concentration of the first lithium salt is 0.5-3 mol / L. The concentration of the second lithium salt is 0.05-0.3 mol / L. The concentration range of the first lithium salt and the second lithium salt is set to help form an appropriate lithium ion concentration gradient, thereby optimizing the ion conduction path and improving the ion conduction efficiency of the electrolyte.
[0068] The mass percentage of the free radical polymerization initiator to the elastomeric polymer monomer ranges from 0.05 wt % to 2 wt %.
[0069] In the embodiment of the present application, the nitrile additive is succinonitrile or glutaronitrile. The free radical polymerization initiator is azobisisobutyronitrile.
[0070] In the embodiment of the present application, the cationic polymerization monomer is a cyclic monomer, and the cationic polymerization monomer includes at least one of dioxane, trioxane, 1,3-dioxolane, tetrahydrofuran and butoxycyclic ring, and the volume percentage of the cationic polymerization monomer and the elastomeric polymer monomer is 5 vol% to 50 vol%.
[0071] It should be noted that cyclic monomers, such as dioxane, have specific chemical structures and can generate linear polymers, thereby enhancing the thermal stability and flame retardancy of the polymer.
[0072] The volume percentage of the cationic polymer monomer and the elastomeric polymer monomer is controlled within the range of 5 vol % to 50 vol %, which can ensure the smooth progress of the polymerization reaction and improve the production efficiency.
[0073] In the embodiment of the present application, the flame retardant initiator includes at least one of tris(pentafluorophenyl)boron or tris(hexafluoroisopropyl)borate. The mass percentage of the initiator to the cationic polymerization monomer ranges from 1wt% to 5wt%.
[0074] It should be noted that the mass percentage of the initiator and the cationic polymerization monomer is controlled within the range of 1wt% to 5wt%, which is helpful to obtain a polymer material with excellent flame retardant properties. The tris(pentafluorophenyl)boron initiator has little impact on the environment during use and meets environmental protection requirements.
[0075] Embodiment 1:
[0076] A method for preparing an electrolyte by in-situ polymerization comprises the following steps:
[0077] In an argon atmosphere, polyethylene glycol diacrylate (PEGDA) and a succinonitrile modifier are added to butyl acrylate respectively to completely dissolve the butyl acrylate to obtain a first solution;
[0078] Adding lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to the first solution, stirring evenly, then adding lithium difluorooxalatoborate (LiDFOB), continuing to stir evenly, and then adding azobisisobutyronitrile as an initiator to obtain an elastomeric polymer electrolyte precursor solution;
[0079] Adding 1,3-dioxolane to the elastomeric polymer electrolyte precursor solution and stirring it evenly, then adding tri(pentafluorophenyl)boron (TFB) as a cationic initiator thereto and stirring it evenly again to obtain a dual polymer electrolyte precursor solution 4;
[0080] After the dual polymer electrolyte precursor solution 4 is injected into the battery, an in-situ polymerization reaction is triggered. The reaction consists of two main steps: the first step is to stand at room temperature for 12 hours, during which 1,3-dioxolane undergoes cationic polymerization; the second step is to heat at 60°C for 12 hours to promote free radical polymerization of butyl acrylate (as an elastomer monomer). After these two steps, the in-situ polymerized dual polymer electrolyte 9 is finally obtained, and this electrolyte converts the battery into a solid-state battery.
[0081] Among them, the battery uses lithium iron phosphate positive electrode and metal lithium sheet negative electrode.
[0082] Comparative Example 1:
[0083] A method for preparing an elastomeric electrolyte comprises the following steps:
[0084] In an argon atmosphere, polyethylene glycol diacrylate (PEGDA) and a succinonitrile modifier are added to butyl acrylate respectively to completely dissolve the butyl acrylate to obtain a first solution;
[0085] Add lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to the first solution, stir well, then add lithium difluorooxalatoborate (LiDFOB), continue stirring well, then add azobis(isobutyronitrile) as an initiator to obtain an elastomeric polymer electrolyte precursor solution; after injecting this solution into the battery, heat it at 60°C for 12 hours to promote free radical polymerization of butyl acrylate, finally obtain an elastomeric electrolyte, and convert the battery into a solid-state battery. This battery uses lithium iron phosphate positive electrode and metal lithium sheet negative electrode.
[0086] Compared with the preparation method of Example 1, the comparative example 1-1 does not add the cationic polymerization monomer and the flame retardant initiator. Figure 3a and Figure 3b It can be seen that the elastomer electrolyte without the addition of a flame-retardant cationic polymerization system is flammable and has poor safety. At the same time, due to the lack of a flame-retardant cationic polymerization system, the contact performance between the elastomer electrolyte and the positive electrode particles is poor, resulting in a significantly lower rate performance than the dual polymer electrolyte 9. Figure 4 As shown in the figure, at small rates (0.1C, 0.2C, 0.5C), the difference in discharge capacity between the two is small; however, at large rates (1C, 2C, 5C), the discharge capacity of Comparative Example 1-1 (without adding flame retardant cationic polymerization system) is 87 mAh g - 1.42.4mAhg - 1 and 15 mAhg - 1, significantly lower than the 126.7 mAhg of dual polymer electrolyte 9 (added with flame retardant cationic polymerization system) - 1.111.9mAhg - 1 and 85.4 mAhg- 1. In addition, Figure 5 As shown, the elastomeric electrolyte impedance (141.85Ω) of Comparative Example 1-1 (without adding the flame retardant cationic polymerization system) is significantly higher than that of the dual polymer electrolyte 9 (104.5Ω).
[0087] Comparative Example 2:
[0088] On the basis of Example 1, tri(pentafluorophenyl)boron (TFB) was replaced with a general cationic initiator, such as aluminum trifluoride, and other components and steps remained unchanged to prepare a dual-polymer elastomeric electrolyte.
[0089] Based on Comparative Example 1, no flame retardant component was added, the electrolyte was easily ignited, and the safety was poor, but the rate performance was significantly improved.
[0090] Comparative Example 3:
[0091] Comparative Example 1, a liquid flame retardant, such as trimethyl phosphate (TMP), is added to the elastomer electrolyte precursor solution, and no cationic polymerization monomer and flame retardant initiator are added. Other components and steps remain unchanged to prepare a liquid additive flame retardant elastomer electrolyte.
[0092] In Comparative Example 3, a liquid flame retardant is added, the mechanical strength of the liquid additive flame retardant elastomer electrolyte is reduced, the ability to inhibit lithium dendrites is weakened, and the cycle life of the solid-state battery using the electrolyte is reduced.
[0093] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other. Each embodiment focuses on the differences from other embodiments.
[0094] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A method for preparing an electrolyte by in-situ polymerization, characterized in that: include: In an argon atmosphere, a cross-linking agent and a nitrile additive are respectively added to the elastomer polymer monomer to completely dissolve the monomers, thereby obtaining a first solution; Adding a first lithium salt to the first solution, wherein the first lithium salt is lithium bis(trifluoromethanesulfonyl imide), lithium hexafluorophosphate or lithium perchlorate, stirring evenly, then adding a second lithium salt, wherein the second lithium salt is lithium difluorooxalatoborate, lithium fluoride or lithium nitrate, continuing to stir evenly, then adding a free radical polymerization initiator to obtain an elastomeric polymer electrolyte precursor solution; Adding a cationic polymerizable monomer to the elastomeric polymer electrolyte precursor solution and stirring it uniformly, then adding a flame retardant initiator thereto and stirring it uniformly again to obtain a dual polymer electrolyte precursor solution; The dual polymer electrolyte precursor solution is added into the battery, and a cationic polymerization reaction is carried out at room temperature. After standing for 10-24 hours, free radical polymerization is initiated by heating to obtain an in-situ polymerized dual polymer electrolyte.
2. The method for preparing an electrolyte by in-situ polymerization according to claim 1, characterized in that: Adding the dual polymer electrolyte precursor solution into a battery also includes: The coating is applied to the positive electrode surface of the battery by dripping, coating or a combination of dripping and coating.
3. The method for preparing an electrolyte by in-situ polymerization according to claim 1, characterized in that: The elastomeric polymer monomer includes at least one of methacrylic acid, ethyl acrylate, ethyl methacrylate, butyl acrylate, and hexyl acrylate.
4. The method for preparing an electrolyte by in-situ polymerization according to claim 1, characterized in that: The crosslinking agent includes a difunctional monomer.
5. The method for preparing an electrolyte by in-situ polymerization according to claim 4, characterized in that: The bifunctional monomer includes at least one of polyethylene glycol diacrylate and tripropylene glycol diacrylate.
6. The method for preparing an electrolyte by in-situ polymerization according to claim 4, characterized in that: The mass percentage of the bifunctional monomer to the elastomeric polymer monomer is 1%-10%.
7. The method for preparing an electrolyte by in-situ polymerization according to claim 1, characterized in that: The concentration of the first lithium salt is 0.5-3 mol / L; the concentration of the second lithium salt is 0.05-0.3 mol / L; the mass percentage of the free radical polymerization initiator and the elastomeric polymer monomer ranges from 0.05wt% to 2wt%.
8. The method for preparing an electrolyte by in-situ polymerization according to claim 1, characterized in that: The nitrile additive is succinonitrile or glutaronitrile; and the free radical polymerization initiator is azobisisobutyronitrile.
9. The method for preparing an electrolyte by in-situ polymerization according to claim 1, characterized in that: The cationic polymerization monomer is a cyclic monomer, and the cationic polymerization monomer includes at least one of dioxane, trioxane, 1,3-dioxolane, tetrahydrofuran and butoxycyclic ring, and the volume percentage of the cationic polymerization monomer and the elastomer polymer monomer is 5 vol% to 50 vol%.
10. The method for preparing an electrolyte by in-situ polymerization according to claim 1, characterized in that: The flame retardant initiator comprises at least one of tris(pentafluorophenyl)boron or tris(hexafluoroisopropyl)borate; the mass percentage of the initiator to the cationic polymerization monomer is in the range of 1wt% to 5wt%.
Citation Information
Patent Citations
Preparation method of in-situ generated semi-interpenetrating network high-voltage polymer electrolyte
CN113745654A
In-situ curing electrolyte and preparation method thereof, and solid-state battery and preparation method thereof
CN114695955A
Solid-state battery and preparation and application of wide-temperature gel electrolyte thereof
CN118352619A
In-situ preparation and application of flame-retardant PDOL-based polymer solid electrolyte
CN118919833A
Solid electrolyte having mechanical gradient and preparation method therefor and application thereof
WO2023108322A1